(untitled) (Journal of Social Sciences Review, 2022)
The current study aims to analyze the withdrawal effects (i.e. psychological and physiological) of methamphetamine on addicts in the Khyber Pakhtunkhwa province of Pakistan. A sample of 180 methamphetamine users was interviewed through an interview schedule by snowball sampling technique. For testing the association between an independent variable (i.e. methamphetamine withdrawal) and dependent variables (i.e. psychological and physiological effects) a Chi-square test was administered. The result illustrates that most of them were youngsters up to 30 years of age, and males and single populations were more exposed to the drug. A significant association were found between methamphetamine/ice withdrawal and psychological effects and physiological effects i.e. fatigue, craving, aggression, depression, irritability, lethargy, poor concentration, sleepiness disorder, psychosis/ hallucinations, loss of pleasure, physical weakness, headaches body pain, watery eyes, runny nose, fatigue, lethargy, dry mouth, diarrhoea and body temperature. The study establishes that methamphetamine/ice is a toxic stimulant drug when a person uses it regularly he/she will face multiple psychological and physical effects when they want to withdraw. The study recommends that government should aware the mass about the toxicity of the drug through mass media and social media and arrange seminars in academic institutions and communities.